Expanding the International Role of China’s Educational Soft Power - Nukitrangsan, Kulnaree (Asia Social Issues, 2024)
The objectives of this research are as follows: (1) to study China’s concept of using soft power to expand its role in international education; (2) to study the mechanisms and operational models used to expand China’s role in international education; and (3) to study the successful outcomes and negative impact of China’s expansion in this field. This is a qualitative research study that utilizes Joseph S. Nye’s concept of soft power in conjunction with document analysis. The research findings indicate that China’s expansion in international education is a tool for using China’s soft power. The mechanisms include establishing branches of the Confucius Institute, recruiting volunteer teachers, setting standards for Chinese language proficiency tests, promoting academic personnel exchange, and providing scholarships for international students. Additionally, China has raised the quality of its domestic educational institutions to meet international standards. China has also established an agency tasked with promoting Chinese language and culture at the international level, namely the Center for Language Education and Cooperation (CLEC), previously known as Hanban. The success of these efforts is evidenced by the number of Confucius Institute branches and classrooms, volunteer teachers, and international students receiving scholarships to study in China. These efforts have resulted in an improved image of China and a reduction in negative perceptions towards China from abroad.